Optimizing Floral Business Sales in Bukittinggi and Surrounding Areas: A Case Study of Eunoia.um Flower Shop's Marketing Strategies - Rahma Maria Sanopa; Zuripal Zuripal (STIE AMKOP, 2023)
In the dynamic landscape of business, effective marketing strategies are vital for sustaining and expanding enterprises. This research focuses on the importance of marketing strategies in the context of